The relationship between student environmental education, knowledge, attitude, and behavior - Nurkhin, Ahmad; Mukhibad, Hasan; Wirawan, Arif Wahyu; Isnarto, Isnarto; Utomo, Asep Purwo Yudi; Saputro, Iwan Hardi; Algifari, Algifari (Journal of Environment and Sustainability Education, 2025)
Environmental sustainability is a crucial concern for universities due to the environmental impacts of their operations, including energy use, waste, and transportation. As key actors, higher education institutions play a vital role in promoting sustainability by enhancing students' knowledge, attitudes, and active participation in sustainable practices. This study aims to analyze the relationship between environmental education, knowledge, attitude, and behavior. A total of 376 students of Universitas Negeri Semarang were involved in this study. Data were collected through questionnaires distributed online. Data analysis was carried out using the PLS-SEM analysis technique. The results showed that environmental attitude has a positive effect on student environmental behavior. However, environmental education and knowledge were not proven to significantly influence environmental behavior directly. Environmental education has been shown to play an important role in significantly increasing knowledge and attitudes towards the environment. In addition, environmental education can indirectly influence environmental behavior through the formation of environmental attitudes. The implication of this study shows that the universities and higher education policymakers need to emphasize strengthening positive attitudes toward the environment in environmental education curricula, rather than just focusing on increasing knowledge alone.